2014
DOI: 10.1103/physreve.89.023210
|View full text |Cite
|
Sign up to set email alerts
|

Rational W-shaped solitons on a continuous-wave background in the Sasa-Satsuma equation

Abstract: We study localized wave on continuous wave background analytically in a nonlinear fiber with higher order effects such as higher order dispersion, Kerr dispersion, and stimulated inelastic scattering. We present an exact rational W-shaped soliton solutions, whose structural properties depend on the frequency of the background field. The hump value increase with the decrease of the background frequency in the certain regime. The highest value of the W-shaped soliton can be nine times the background's, and the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 33 publications
(30 reference statements)
3
43
2
Order By: Relevance
“…What should be pointed out that, most of the single localized wave solutions have been obtain in the previous literature. For the focusing case, the breather solution [1,30], rogue wave solution [4], rational W-shape soliton [34] and degenerate resonant soliton on NVBC [32] have been obtained in the previous literature. For the defocusing case, the dark soliton and W-shape dark soliton (dark double-hump soliton) have been been obtain through bilinear method and symbolic computation [12].…”
Section: 1mentioning
confidence: 99%
“…What should be pointed out that, most of the single localized wave solutions have been obtain in the previous literature. For the focusing case, the breather solution [1,30], rogue wave solution [4], rational W-shape soliton [34] and degenerate resonant soliton on NVBC [32] have been obtained in the previous literature. For the defocusing case, the dark soliton and W-shape dark soliton (dark double-hump soliton) have been been obtain through bilinear method and symbolic computation [12].…”
Section: 1mentioning
confidence: 99%
“…1 (c)], and anti-eye-shaped one [ Fig. 2 [26,27]; otherwise, the rational solution demonstrates W-shaped soliton behavior [28] for the nonlnear fiber with high-order effects. It was also demonstrated that relative frequency can vary MI properties and induced RWs in coupled defocusing NLS [29].…”
Section: Spectrum Analysis Of Different Rogue Wave Patternsmentioning
confidence: 99%
“…During the past few decades, the cosmological principle had been tested many times and found to be well consistent with most cosmological observations, for instance, the halo power spectrum [2], the statistics of galaxies [3], the cosmic microwave background (CMB) radiation from Wilkinson Microwave Anisotropy Probe (WMAP) [4,5] and Planck satellites [6][7][8]. However, there still exist some phenomena which are inconsistent with the cosmological principle, such as the alignment of quasar polarization vectors on large scale [9], the spatial variation of the fine structure constant [10,11] and MOND acceleration scale [12][13][14], the anisotropic accelerating expansion of the Universe [15][16][17][18][19][20], the alignment of CMB quadrupole and octopole [21][22][23], the hemispherical power asymmetry in CMB [24][25][26][27], and parity asymmetry in CMB [26][27][28][29][30][31]. In particular, hemispherical power asymmetry, initially observed in WMAP [4,5], has come to be one of the outstanding anomalies that indicated violation of statistical isotropy on large angular scales of CMB sky.…”
Section: Introductionmentioning
confidence: 99%